Isolation of Escherichia coli from raw milk and detection of antibiotic resistance genes by blaTEM PCR - Patange, Varsha; Thorat, Varsha Devidas (Indian Journal of Dairy Science, 2022)
Escherichia coli is an important pathogen that causes urinary, gastrointestinal infections and septicaemia. The present study aimed to identify the prevalence of E. coli in raw milk samples and relate the results with public health implications of the infection. A total of 106 raw milk samples of cattle and buffalo were collected from the local vendors and organized as well as unorganized dairy farms in and around the Mumbai region. Total coliform count and isolation ofÂ E. coli from milk samples was done on MacConkey and Eosin Methylene blue agar. The recovered isolates were subjected to a blaTEM PCR assay. The results showed that the total coliform count range was from 3.7x105 to 1.2x106, 2.6x105 to 1.8x106, 3.6x105 to 1.48x107, 4.4x105 to 6.2x106, and 4.9x105. The rate of isolation ofÂ E. coliÂ from raw milk samples in our study was 39.62 %. In vitro antimicrobial sensitivity testing ofÂ E. coliÂ showed that 92.85% of the isolates were sensitive to Ciprofloxacin, followed by 69.04% to Imipenem, 66.66% to Amikacin, 59.52% to Ceftriaxone, 57.14% to Tetracycline and 11.90% to Amoxicillin + clavulanic acid. Whereas 88.09% of the isolates were resistant to Amoxicillin + clavulanic acid followed by 42.85% to Tetracycline, 40.47% to Ceftriaxone, 33.33% to Amikacin, 30.95% to Imipenem and 7.14% to Ciprofloxacin. Out of 42 isolates, ten isolates (23.8%) showed a blaTEM gene-specific amplicon of 1215 bp. There is a need to reduce the contaminants by implementing appropriate measures as resistant E. coli contaminated raw milk samples were found in the Mumbai region.